Komunikasi Online Remaja dengan Orang Tuanya yang Bekerja Berperan dalam Meningkatkan Kepuasan Hidup - Nurul Adabina; Eko Handayani (Jurnal Ilmu Perilaku, 2021)
Abstract. Communication with parents is one of several factors related to adolescents’ life satisfaction. Parental work pressures that hinder parents from communicating with adolescents can be reduced through online communication. The purpose of this research was to examine the role of online parent-child communication in life satisfaction among adolescents with working parents. A total of 106 adolescents aged 10-15 years with working parents participated in this research. Parent-child online communication was measured using a modified version of Online Parent-Child Communication, while Life Satisfaction was measured using the Satisfaction with Life Scale Adapted for Children. The results showed parent-child online communication had a significant and positive effect on life satisfaction among adolescents with working parents. In addition, this research also found a significant and positive effect between parent-child online communication and life satisfaction of male and female adolescents with working parents. Therefore, parents should optimize online communication with their adolescents when they are working because online communication gives an impression of parental support, which contributes to increasing adolescents’ life satisfaction.